Comparison of actual evaporation from water surface measured by GGI-3000 evaporimeter with values calculated by the Penman equation - KOHUT, Mojmír; ROŽNOVSKÝ, Jaroslav; KNOZOVÁ, Grazyna (Contributions to Geophysics and Geodesy, 2014)
Information about water evaporation is essential for the calculation of water balance. Evaporation, however, is a very complex physical process and it is therefore difficult to quantify. Evaporation measurements from the weather station network of the Czech Hydrometeorological Institute between 1968 and 2011 were performed using the evaporimeter GGI-3000. Evaporation was calculated using modified standard method based on FAO. The aim of the article was to compare the measured values and calculations. It has been found that the evaporation values from water surface calculated using the empirical equation are usually higher than the measured values by on average 0.8 mm, in extreme cases even 6.9 mm. The measured data shows higher variability than the calculated values, which means that correlations between series are not strong, the correlation coefficient being 0.7. Nevertheless the findings can be used for homogenization of series measured by the GGI-3000 evaporimeter.